(untitled) (Journal of the College of Education for Women, 2019)
This study aims to recognize the most common thinking styles and level of the need for cognitive university students , the relation between thinking styles and the need for cognitive, and there are differences according to gender .The sample consists of (250) males and females university students for the academic year (2013-2014), and the researcher uses two scales;" thinking styles scale (Harison &Bramson, 1986), and the need for cognitive scale" (Cacioppo, Petty & Kao , 1996).The results show that there is difference in the range of the prevalence of the thinking styles among university students , the scientific thinking style is the most common , the students have got the arrange level of the need for cognitive , and there is statistically correlation between thinking styles and the need for cognitive .